Minimal and zero liquid discharge with reverse osmosis using low-salt-rejection membranes. (1st March 2020) - Wang, Zhangxin; Deshmukh, Akshay; Du, Yuhao; Elimelech, Menachem
Abstract: Minimal and zero liquid discharge (MLD/ZLD) are wastewater management strategies that are attracting heightened attention worldwide. While conventional reverse osmosis (RO) has been proposed as a promising technology in desalination and MLD/ZLD processes, its application is limited by the maximum hydraulic pressures that current RO membranes and modules can withstand. In this study, we develop low-salt-rejection RO (LSRRO), a novel staged RO process, that employs low-salt-rejection membranes to desalinate or concentrate highly saline feed streams, requiring only moderate hydraulic pressures. Based on process modeling, we demonstrate that LSRRO can overcome the hydraulic pressure limitations of conventional RO, achieving hypersaline brine salinities (>4.0 M NaCl or 234 g L −1 NaCl) that are required for MLD/ZLD applications, without using excessively high hydraulic pressures ( ≤ 70 bar ). In addition, we show that the energy efficiency of LSSRO is substantially higher than traditional thermally-driven phase-change-based technologies, such as mechanical vapor compressor (MVC). For example, to concentrate a saline feed stream from 0.1 to 1.0 M NaCl, the specific energy consumption ( S E C ) of 4-stage LSRRO ranges from 2.4 to 8.0 kWh of electrical energy per m 3 of feedwater treated, around four times less than that of MVC, which requires 20–25 kWhe m −3 . Furthermore, compared to osmotically mediated RO technologies that require bilateral countercurrent stages to treat hypersaline brines, LSRRO is eminently more practical as it can be readily implemented by using 'loose' RO or nanofiltration membranes in conventional RO. Our study highlights LSRRO's potential for energy efficient brine concentration using moderate hydraulic pressures, which would drastically improve the energetic and economic performance of MLD/ZLD processes. Graphical abstract: Image 1 Highlights: We develop a novel staged RO technology using low-salt-rejection membranes (LSRRO). LSRRO can concentrate high salinity wastewaters with moderate hydraulic pressures. Energy efficiency of LSRRO is significantly greater than thermal processes. Implementation of LSRRO is easier than other osmotically mediated technologies. LSRRO has the potential to advance minimal/zero liquid discharge processes.